SCIENTIFIC AND THEORETICAL FUNDAMENTALS OF MODERN EDUCATIONAL TECHNOLOGY - Fuzailova Gavxar Siddikovna (Galaxy International Interdisciplinary Research Journal, 2021)
The modern education system, its goals, and objectives must be consistent with the solution of the problem of education, which serves the development of our republic. Information on the intellectual potential of people in the management of socio-economic development of the country and in determining its future shows the great importance of the prevailing scientific and technological progress in the world. At the same time, the current state of science development in the world, especially in a society where modern information technologies are widely introduced, the rapid updating of knowledge in various fields, puts students in front of them the task of regular and independent search for knowledge.